Clinical impact of hydroxychloroquine dose adjustment according to the American Academy of Ophthalmology guidelines in systemic lupus erythematosus. Issue 1 (19th May 2020) - Vázquez-Otero, Ileana; Medina-Cintrón, Nicolle; Arroyo-Ávila, Mariangelí; González-Sepúlveda, Lorena; Vilá, Luis M
Abstract : Objective: The American Academy of Ophthalmology recommends a maximum hydroxychloroquine (HCQ) dose of ≤5.0 mg/kg/day to reduce the risk of HCQ-induced retinopathy. To determine if this dose adjustment would have an impact on the clinical course of SLE, we compared outcome measures in a cohort of patients with SLE before and after adjusting HCQ dose. Methods: Sixty Puerto Ricans with SLE (per 1997 American College of Rheumatology criteria) treated with HCQ who were changed to HCQ ≤5.0 mg/kg/day were studied. Visits were ascertained every 6 months for 2 years before and 2 years after HCQ dose adjustment (baseline visit). Disease activity (per Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)), SLE exacerbations, emergency room visits, hospitalisations, disease damage (per Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index), corticosteroids exposure, prednisone dose and immunosuppressive drugs exposure were determined before and after HCQ dose change. Results: At baseline visit, the mean age was 43.8±15.1 years. All patients were women. The mean disease duration was 13.8±9.1 years. After HCQ dose adjustment, patients required a lower prednisone dose when compared with visits before HCQ dose reduction. No significant differences were observed for mean SLEDAI scores, lupus exacerbations, emergency room visits, hospitalisations, disease damage and exposure to immunosuppressive drugs before and after HCQ dose adjustment. Conclusions: This study suggests that adjustment of daily HCQ dose to ≤5.0 mg/kg/day of actual body weight does not have a significant impact on the short-term and mid-term outcomes in this group of patients with SLE.